Design of Contest for Educational Underwater Robot for STEM: Learning Applying Modeling Based on Control Engineering - Yamagata, Hirokazu; Morita, Toshio (Journal of robotics and mechatronics, 2017)
To apply science, technology, engineering, and mathematics (STEM) education effectively, it is necessary to prepare a core that would combine its four elements and to place it centrally in an educational activity. The present authors have previously conducted an educational activity, the core of which comprised model construction using free-body diagrams (FBDs); this activity was targeted at a small group of learners. The authors employed underwater robots as the instructional material, and confirmed that positive learning effects can be produced. In the present study, we used a block diagram to construct a model of educational activities to educate participants by introducing an underwater robot and FBDs to a large group of learners, simultaneously. In addition, we designed an educational program, which ensured that the configuration would remain potent when expanded to large groups, aiming toward ensuring the educational effects. We hosted a contest based on this configuration, then evaluated the results qualitatively – by observing the participating students – and quantitatively – by conducting a questionnaire survey – to verify the effects. As a result, it was confirmed that consistency can be obtained even if the conventional educational method is extended to a larger number of student.